CHALLENGES AND OPPORTUNITIES IN DOING BUSINESS IN ASIAN COUNTRIES FOR MULTINATIONAL COMPANIES: A LITERATURE REVIEW - Septriana Zhang (Politeknik Bisnis Indonesia, 2023)
The countries of Indonesia, Singapore and Malaysia are part of The Association of Southeast Asian Nations (ASEAN), which was formed on August 8, 1967 by Indonesia, Malaysia, the Philippines, Singapore and Thailand. The purpose of this research is to increase and expand the reader's knowledge about the business of the three countries in Asia such as Southeast Asia. The method used is a literature review found from various sources, both journals, books, articles, and so on. In carrying out a business, especially expanding abroad, of course, companies must know or consider things such as the convenience or benefits that can be obtained or what challenges/obstacles must be overcome if they want to expand their business network, as we know that every country has different cultures. , social, political, economic provisions and government regulations. Therefore, the ease and constraints of doing business in ASEAN countries will be analyzed. whether in Indonesia, Singapore or Malaysia, each country has its challenges but there are also conveniences that can attract other foreign companies to do business in their country.